USE OF SYNTHETIC FORMS IN THE PRESERVATION AND EXPLOITATION OF THE GENE POOL OF WILD COMMON WHEAT RELATIVES - R. O. Davoyan; I. V. Bebyakina; O. R. Davoyan; A. N. Zinchenko; E. R. Davoyan; A. M. Kravchenko; Y. S. Zubanova (Вавиловский журнал генетики и селекции)
The results of investigation and exploitation of the synthetic genome addition line T. miguschovae (Triticum militinae /Aegilops tauschii) and genome substitution lines Avrodes, Avrosis, Avrolata, Avrotata, Avroale, and Avrocum are reported. In the genome substitution forms, genomes of Ae. speltoides, Ae. sharonensis, Ae. umbellulata, Ae. uniaristata, Secale cereale and Agropyron glaucum are substituted for the D-genome of common wheat cultivar Avrora. The synthetic forms provide a unique genetic basis for preservation and use of the gene pool of wild relatives in wheat breeding. These forms have been used to produce secondary recombination synthetic forms (RS forms) with genome constitutions BBAADS, BBAASR and BBAASSsh. These cytologically stable introgression lines combine disease resistance and high protein content. Five common winter wheat cultivars have been developed on the base of the introgression lines obtained.